FENOMENA PERSAMPAHAN DI LINGKUNGAN KECAMATAN KERTAPATI KOTA PALEMBANG - Helfa Septinar (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The background of this research is carried out because of the unusual phenomenon that researchers see. That is the spread of household garbage that is usually seen around the house, on the roadside or in the river, but this is the spread of household waste along the middle of the road or in the middle of the street. The purpose of this study is to find out why there is a phenomenon of distribution of garbage in the middle of the road section District Kertapati Kemang Agung and Kemas Rindo. The method used is qualitative descriptive method. The result of this research is that the garbage provided is too little and the location is far apart and the other, the type of garbage found is the type of household garbage, which disposes the garbage at the location is the community, the community is awkward with the waste, the emergence of environmental pollution like smell the sting and the unhealthy environment, and the environment is less comfortable, and the conclusion of this research is the phenomenon of this garbage occurred due to lack of pasilitas-pasilitas cleanliness, place of garbage collecting and the opportunity to dispose of garbage in less appropriate place in District Kertapati Kemang Agung and Kemas Rindo. Keywords—Phenomena, garbage, environment